1997
DOI: 10.1002/art.1780401119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulse methylprednisolone on bone and marrow tissues. Corticosteroid‐induced osteonecrosis in rabbits

Abstract: Objective. To investigate the effects of pulse methylprednisolone acetate on bone and bone marrow tissues and to clarify the causal factors of corticosteroidinduced osteonecrosis (ON) by using an experimental animal model.Methods. Male adult Japanese white rabbits were injected once with 20 mg/kg of methylprednisolone into the right gluteus medius muscle. Seven rabbits were killed at 4 weeks, 4 at 6 weeks, 4 at 8 weeks, and 6 at 10 weeks. Both histopathologic and hematologic studies were performed every week.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
181
4
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(192 citation statements)
references
References 26 publications
5
181
4
1
Order By: Relevance
“…This lead to chondrous ossification defects histopathologically compatible to our findings. FH necrosis was found after a single high-dose methylprednisolone injection in adult rabbits [42]. In contrast to the present findings, previous work has shown a 2-3 fold decrease of FH blood flow after 2 weeks of high dose intramuscular methylprednisolone treatment in immature pigs [7].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This lead to chondrous ossification defects histopathologically compatible to our findings. FH necrosis was found after a single high-dose methylprednisolone injection in adult rabbits [42]. In contrast to the present findings, previous work has shown a 2-3 fold decrease of FH blood flow after 2 weeks of high dose intramuscular methylprednisolone treatment in immature pigs [7].…”
Section: Discussioncontrasting
confidence: 99%
“…No histologic signs of FHN were found in the present material. The steroid dosage in the present study was lower and maintained longer than in the previous study and than in studies in rabbits in which osteonecrosis was found [42]. Using the same methylprednisolone protocol as in the present study, the authors have found decreased vertebral endplate and cancellous bone blood flow in growing pigs [6] which may be due to the different blood supply [37].…”
Section: Discussionsupporting
confidence: 49%
“…We used a rabbit model of corticosteroid-induced osteonecrosis (Yamamoto et al 1997). 2 weeks after the start of feeding and after allocation of the rabbits into the 2 groups, a high dose of methylprednisolone acetate (MPSL) (20 mg/kg body weight; Pfizer Japan Inc., Tokyo, Japan) was administered once into the right gluteus medius muscle of all the rabbits to induce osteonecrosis.…”
Section: Methodsmentioning
confidence: 99%
“…When the two examiners did not agree, they discussed the findings (still blind) to reach a consensus. A positive diagnosis of osteonecrosis was determined based on the diffuse presence of empty lacunae or pyknotic nuclei of osteocytes within the bone trabeculae, accompanied by surrounding bone marrow cell necrosis or fat cell necrosis (Yamamoto et al 1997). Empty lacunae of osteocytes within the bone trabeculae without bone marrow cell necrosis or fat cell necrosis was not diagnosed as osteonecrosis.…”
Section: Methodsmentioning
confidence: 99%
“…Osteonecrotic areas were identified as diffusely empty lacunae or pyknotic nuclei of osteocytes in the bone trabeculae, accompanied by surrounding necrosis marrow. (43) Appositional bone formation with osteoblast-like cells around the osteonecrotic lesion was classified as reparative osteogenesis, whereas fibrotic tissue creep linked to necrotic bone resorption was classified as destructive repair. (30) Evaluation of the repair pattern was done as follows: the entire area of each section, including epiphysis and metaphysis, was examined based on the characteristic histopathological features blindly by two pathologists.…”
Section: Microangiographymentioning
confidence: 99%